Considerazioni sui lettori di Montesquieu (XVIII-XX secolo) - Venturelli, Piero (Montesquieu.it, 2009)
This article in meant to bring a contribution to the study of the penetration of Montesquieu’s ideas and theories starting from Montesquieu e i suoi interpreti (a cura di D. Felice, 2 tt., Pisa, ETS, 2005). The most relevant interpretations or uses of the philosopher’s work of the last two hundred and fifty years will be put together with particular reference to the Esprit des Lois (1748). We consider France, Great Britain, North America, Germany and Italy as the linguistic and cultural areas where Montesquieu’s thought is stronger and more lasting. Over forty authors have been taken into consideration: J.-B. le Rond d’Alembert, D. Hume, J.-J. Rousseau, C. Beccaria, A. Genovesi, E. Personè, D. Diderot, L. de Jaucourt, E. Gibbon, J.G. Herder, G. Filangieri, Th. Jefferson, A. Hamilton, J.-A.-N. Caritat de Condorcet, L. Saint-Just, B. Constant, G.W.F. Hegel, A. de Tocqueville, H. Taine, F. Sclopis di Salerano, É.-R. Lefebvre de Laboulaye, F. Meinecke, Ch. Eisenmann, J. Starobinski, L. Althusser, H. Arendt, R. Aron, R. Shackleton etc. In this article, Voltaire, E. Burke, L.-C. Destutt de Tracy, A. Comte, É. Durkheim and S. Cotta have been considered more in detail.